Place of Birth: Why Urban Women Still Prefer Home Deliveries? - M.S.R. Murthy, P. Vinayaka Murthy, M. Hari, V.K.R. Kumar and K. Rajasekhar (J. Hum. Ecol., 21(2): 149-154 (2007), 2007)
In spite advances in medical care and services urban women prefer home deliveries followed by public facility compared to private facility. The NFHS-1 and 2 data are utilized for this analysis. The reasons are many. Multinomial regression it revealed that a good proportion of short-term migrants, respondents with low levels of education, lack of media exposure (radio, News paper reading, and T.V), low standard of living, SC/ST, are more log odds of using home and public facility than private facility. Further, a good proportion of Hindus preferred home and public facility in comparison to private facility during 1991 (NFHS-1) whereas it is quite opposite during 1999 (NFHS-2) with reference to other religious populations. The log odds are more prominent for home deliveries with reference to private facility. The log odds are somewhat less prominent for public facility with reference to private facility. It shows that some public facilities are functioning well. Though private facility is expensive women with good standards of living, media exposed, and higher levels of education have favoured private facility